Analysis and forecasting of shoreline changes in Amurang Bay - Joyce C Kumaat,; Eirene V M Rembet, (Technium Social Sciences Journal, 2023)
Amurang Bay has a very high development potential with the characteristics of a sloping and shallow topography and one of the areas as the capital of the South Minahasa district which is vulnerable to changes in the coastline. This analysis is used in order to analyse the changes that occur to the coastline in Kawangkoan Bawah and to see the changes over the next 10 years. Changes in the coastline can be monitored using remote sensing satellite technology, in a multi-temporal method as the comparative method or time series image analysis (last 5 years). The data analysis technique was carried out through ArGIS software using an additional tool, named DSAS. results of analysis of shoreline changes using NSM and LRR calculations in 2017-2022. Overall, the indications are that abrasion and accretion always occur every year so that they can change the shape of the beach over the last 5 years. The speed of movement of the coastline -5.9m/year. As for the speed of retreat of the coastline is -0.37m/year. The results of observation and analysis show that the coastline of Kawangkoan Bawah Village in Teluk Amurang is basically dynamic because it is found that abrasion and accretion occur every year. Recommended further studies related to land use patterns, sea level rise, and morphological changes to the existence and sustainability of the coast. We also recommend conducting in-depth studies that rely on field measurements to include the effect of momentary water levels in shoreline position monitoring